CA 15-3 may be a promising biomarker for differentiating distant organ metastasis in breast cancer at initial diagnosis - Yilmaz, Serkan; Yur, Mesut (Bmc, 2025)
Background Imaging techniques for breast cancer identify distant organ metastasis, but can be time-consuming and costly. This study compares clinicopathological and laboratory data between metastatic and nonmetastatic breast cancer patients at initial diagnosis and evaluates CA 15 - 3's predictive value for distinguishing distant metastases. Methods This retrospective study examined 232 untreated breast cancer patients diagnosed between January 2021 and January 2022. They were divided into distant organ metastatic (Group I) and nonmetastatic (Group II) at the initial diagnosis. We analyzed laboratory data, including CA 15 - 3 and CEA levels, and used Receiver Operating Characteristic (ROC) curves to find optimal cut-off values for predicting distant organ metastasis. Results Forty-nine patients (21.1%) had distant organ metastases at initial diagnosis. Significant differences were found between groups in tumor diameter, neutrophil and lymphocyte counts, T-stage, N-stage, CA 15 - 3, CEA, albumin, alkaline phosphatase, neutrophil-to-lymphocyte ratio, and the systemic immune inflammation index (SII) (all p < 0.05). CA 15 - 3 demonstrated excellent discriminatory ability (AUC = 0.950; 95% CI: 0.924-0.975; p < 0.001). A CA 15 - 3 cutoff value of 25.8 U/mL had 100% sensitivity, 82.5% specificity, 60.5% positive predictive value, and 100% negative predictive value. No patient with a CA 15 - 3 level below 25.8 U/mL presented with distant organ metastasis. Conclusions CA 15 - 3 demonstrated promising performance in ruling out distant metastases in newly diagnosed breast cancer patients. Further prospective studies are needed to confirm whether using CA 15 - 3 may reduce the time loss and costs associated with routine imaging for distant organ metastasis.
Keywords: Breast cancer; Metastasis; CA 15-3; CEA; Biomarker